PENGARUH BAURAN PRODUK MUSEUM TERHADAP KEPUTUSAN BERKUNJUNG WISATAWAN DI MUSEUM JAWA TENGAH RANGGAWARSITA: Survei pada Pengunjung Umum di Museum Jawa Tengah Ranggawarsita - Arief, Rahman (2013)
Kota Semarang merupakan salah satu Kota di Jawa Tengah yang memiliki potensi wisata yang cukup tinggi dan salah satu destinasi yang dapat dikunjung di Kota Semarang yaitu Museum Jawa Tengah Ranggawarsita yang telah memberikan kontrbusi terhadap perkembangan pariwisata Kota Semarang, namum pada tahun 2012 Museum Jawa Tengah Ranggawarsita mengalami penurunan tingkat kunjungan hingga -3 %. Hal tersebut diduga karena faktor keputusan berkunjung wisatawan. Oleh karena itu Museum Jawa Tengah Ranggawarsita perlu memperhatikan bauran produk Museum yang terdiri dari Core product, facilitating product, supporting product, physical environment, customer interaction with service delivery system, customer interaction with others customer, and customer coproduction. dalam rangka meningkatkan keputusan berkunjung wisatawan di Museum Jawa Tengah Ranggawarsita. Berkaitan dengan hal tersebut, maka dilakukan penelitian mengenai pengaruh bauran produk Museum terhadap keputusan berkunjung wisatawan di Museum Jawa Tengah Ranggawarsita sebagai Museum Jawa Tengah Ranggawarsita. Masalah yang diteliti dalam penelitian ini adalah bagaimana tanggapan pengunjung mengenai bauran produk Museum yang terdiri dari Core product, facilitating product, supporting product, physical environment, customer interaction with service delivery system, customer interaction with others customer, and customer coproduction. Serta bagaimana tanggapan pengunjung terhadap keputusan berkunjung wisatawan Museum Jawa Tengah Ranggawarsita sebagai Museum Jawa Tengah, dan bagaimana pengaruh bauran produk Museum terhadap keputusan berkunjung wisatawan di Museum Jawa Tengah Ranggawarsita sebagai Museum Jawa Tengah Ranggawarsita. Populasi penelitian ini adalah Jenis Pengunjung Museum Jawa Tengah Ranggawarsita. Teknik pengembilan sampel adala sampling sistematis. Metode yang digunakan adalah deskriptif dan explanatory survey. Data yang digunakan adalah data primer dan data sekunder. Teknik analisis yang dugunakan adalah analisis regresi sederhana (simple regresion). Pengujian hipotesis menunjukan bahwa bauran produk Museum berpengaruh secara signifikan terhadap keputusan berkunjung wisatawan di Museum Jawa Tengah Ranggawarsita sebagai Museum Jawa Tengah. Kata kunci: bauran produk, keputusan berkunjung Semarang city is the one of central java's city which have big tourism potential. The one of destination is museum. Semarang city have many museum, one of the museum is Museum Central Java's Ranggawarsita. Museum Central Java's Ranggawarsita gave the contribution to semarang's tourism development. However, in 2011 Museum Central Java's Ranggawarsita visit rates decreased by -3 %. It is suspected because of the decision of visiting tourist. Therefore, Museum Central Java's Ranggawarsita need to pay attention to the product mix consisting of museum of Core product, facilitating product, supporting product, physical environment, customer interaction with service delivery system, customer interaction with others customer, and customer coproduction. In order to improve decisions tourists visiting the Museum Central Java's Ranggawarsita. Related to phenomena, thus it done research about the effect of tourism product mix to travelers visiting the museum decisions in Museum Central Java's Ranggawarsita As central java's historical museum. The problem that thorough in this research is how the conception of museum cental java's ranggawarsita's visitor about tourism product mix of museum central java's ranggawarsita which consist of Core product, facilitating product, supporting product, physical environment, customer interaction with service delivery system, customer interaction with others customer, and customer coproduction. How the conseption of museum central java's ranggawarsita visitor to decisions visited tourist of museum central java's rangawarsita historical museum, and how the effect of tourism product mix to decisions visited tourist of museum cental java's ranggawarsita as central java's ranggawarsita museum. Tecnique of sampling that used is systematic sampling technique. The method in that used in this reseacrh is descriptive and explanatory survey. The data that used is primary data and secondary data. Technique analysis that used is simple regresion analysis. The result of hypothesis examination indicated taht there is effect of tourism product mic to decisions visited tourist of museum central java's ranggawarsita as central java's historical museum. Keyword: product mix , decisions visiting.